Awareness and the Demand for Environmental Quality: Drinking Water in Urban India - Jyotsna Jalan, E. Somanathan and Saraswata Chaudhuri (BREAD Working Paper No. 049, 2003)
The demand for environmental quality is often presumed to be low in developing countries due to poverty. Less attention has been paid to the possibility that lack of awareness about the adverse health effects of environmental pollution could also keep the demand low. We use a household survey from urban India to estimate the effects of awareness and wealth on home water purification. Average costs of different home purification methods are used to get estimates on willingness to pay for better drinking water quality in Delhi. We find that measures of awareness such as schooling and exposure to mass media have statistically significant effects on adoption of different home purification methods and therefore, on willingness to pay. These effects are similar in magnitude to the wealth effects.